Some considerations on the challenges to the economic science - Irina Mădălina Doroftei (Romanian Journal of Fiscal Policy (RJFP), 2012)
The recent crisis of 2008 has revealed several challenges for the economic science, sparking a considerable amount of debate regarding the profession of economists and the role of macroeconomics and monetary policies. The first question that arose was why there was a lack of anticipation of the crisis (especially from the mainstream economists) and, secondly, how could policy makers fix the economy after the crash of the markets. The metaphor economics as a machine is a good reflection of how people think of the economy and economists today, although the author of this paper, among many other researchers, believes otherwise. Therefore, this paper gives preliminary answers to the questions above and describes today's challenges to macroeconomic models and to monetary policy frameworks in particular, in terms of methodology.
Keywords: B41; E58; G01; G10; H12; 330; economic methodology; financial crisis; monetary policy